Endurance training improves responsiveness to insulin and modulates insulin signal transduction through the phosphatidylinositol 3-kinase/Akt-1 pathway - Luciano, E.; Carneiro, E. M.; Carvalho, CRO; Carvalheira, JBC; Peres, S. B.; Reis, MAB; Saad, MJA; Boschero, A. C.; Velloso, L. A. (Bio Scientifica Ltd, 2002)
Background: Endurance training increases insulin-stimulated muscle glucose transport and leads to improved metabolic control in diabetic patients.Objective: To analyze the effects of endurance training on the early steps of insulin action in muscle of rats. Design: Male rats submitted to daily swimming for 6 weeks were compared with sedentary controls. At the end of the training period, anesthetized animals received an intravenous (i.v.) injection of insulin and had a fragment of their gastrocnemius muscle excised for the experiments.Methods: Associations between insulin receptor, insulin receptor substrates (IRS)-1 and -2 and phosphatidylinositol 3-kinase (PI3-kinase) were analyzed by immunoprecipitation and immunoblotting. Akt-1 serine phosphorylation and specific protein quantification were detected by immunoblotting of total extracts, and IRS-1/IRS-2-associated PI3-kinase activity were determined by thin-layer chromatography.Results: Insulin-induced phosphorylation of IRS-1 and IRS-2 increased respectively by 1.8-fold (P < 0.05) and 1.5-fold (P < 0.05), whereas their association with PI3-kinase increased by 2.3-fold (P < 0.05) and 1.9-fold (P < 0.05) in trained rats as compared with sedentary controls, respectively. The activity of PI3-kinase associated with IRS-1 and IRS-2 increased by 1.8-fold (P < 0.05) and 1.7-fold (P < 0.05) respectively, in trained rats as compared with their untrained counterparts. Serine phosphorylation of Akt-1/PKB increased 1.7-fold (P < 0.05) in trained rats in response to insulin. These findings were accompanied by increased responsiveness to insulin as demonstrated by a reduced area under the curve for insulin during an i.v. glucose tolerance test, by increased glucose disappearance rate during an insulin tolerance test, and by increased expression of glucose transporter-4.Conclusions: the increased responsiveness to insulin induced by chronic exercise in rat skeletal muscle may result, at least in part, from the modulation of the insulin signaling pathway at different molecular levels.